Local thermal effect on vapor extraction (VAPEX) for heavy oil enhanced recovery - Esmaeili, A. (Institution of Engineering and Technology, 2015)
Heavy oil has a high viscosity, so production form heavy oil reservoir is very difficult. One of the methods which are used to increase recovery factor from this reservoirs is miscible injection. Among miscible injection methods is vapor extraction method via injection the vapor of hydrocarbon solvent which is a suitable constitute for thermal methods in reservoir where heat loss is high. The vapor extraction (VAPEX) process, a solvent-based enhanced oil recovery process has been found promising for some heavy oil reservoirs. Viscosity of heavy oil will be decreased by injection the vapor of hydrocarbon solvent into it. This phenomenon is the base of vapor extraction (VAPEX) method. One of the disadvantages of VAPEX process which has been reported by most of previous researchers is its low production rate. In this paper, effect of temperature on increasing recovery and production rate of this process has been investigated. Obtained results show that by increasing temperature, oil recovery and production rate by this process will be increased.